Self-monitoring framework for patients in IoT-based healthcare system - Ramalingam, Mritha; Puviarasi, R.; Chinnavan, Elanchezhian; Foong, H. K. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
With the recent developments in Internet of Things (IoT) and the increase of smartphone users, patient’s health can be monitored without visiting the hospital for medical services. Nowadays, the cost of healthcare is high and insufficient of workforce in the hospital caused the patient unwilling to visit the hospital. The proposed work is to design a monitoring system using sensor and microcontroller to be used by the patients at their place (eg. home). This paper discusses the designing process of the framework. This system will allow the patient to measure their pulse rate and body temperature by using sensors and data collected from the sensor are integrated by using a microcontroller. These acquired patients data could be viewed in mobile application. In addition, the system will provide features such as consultation or chat facility and medical reminder to further improve the feasibility of patients’ health care system.